Improved heat stability of recombined filled evaporated milk emulsions by wet heat pre-treatment of skim milk powder dispersions at different pH values. (15th January 2022) - Wu, Jianfeng; Chen, Simin; Nyiransabimana, Lydivine; Van Damme, Els J.M.; De Meulenaer, Bruno; Van der Meeren, Paul
Abstract: In this study, skim milk powder (SMP) dispersions were subjected to wet heat pre-treatment at 80 °C at pH 6.6, 7.1 and 7.6 to improve the heat stability of recombined filled evaporated milk (RFEM) emulsions. The results of free amino group content, Amadori products formation and color measurement revealed that the Maillard conjugation was generally faster at higher pH. SDS-PAGE clearly implied the conjugation of whey proteins upon wet heating at different pH values. Non-sedimentable protein content and composition analysis showed that extensive casein dissociation from micelles was found upon wet heat incubation at pH 7.1 and 7.6. The obtained SMP dispersions were subsequently used to prepare RFEM emulsions. The heat stability of RFEM emulsions derived from SMP dispersions incubated at pH 6.6 and 7.6 was improved greatly upon selecting an appropriate incubation time, while the heat stability improvement was less distinct upon incubation at pH 7.1. Furthermore, the incubation time needed to obtain a heat-stable RFEM emulsion against heating at 120 °C for 30 min was shorter at pH 7.6 as compared to the original pH 6.6 (0.5 h versus 2 h). On the other hand, prolonged incubation had a detrimental effect on the heat stability of RFEM. Graphical abstract: Image 1 Highlights: Wet heat incubation of skim milk powder gave rise to protein-lactose conjugates. Heat stability of recombined filled evaporated milk was improved upon incubation. Best improved heat stability was found upon incubation at pH 7.6 to 8.0 Prolonged incubation had a negative effect on the heat stability at all pH.